MENELISIK AKAR PENYEBAB KEKERASAN GENDER PADA MASYARAKAT PETANI PELADANG KECAMATAN GEDANGAN KABUPATEN MALANG - Khoirul Asfiyak (JAS : Jurnal Ahwal Syakhshiyyah, 2021)
Gender-based violence often occurs in social life both in urban areas and in rural areas. The government has been trying to reduce the rate of this gender based crime. However, incidents like this have always been repeated in various places in Indonesia. In Malang regency, gender-based violence often occurs with all the contributing factors. This incident is interesting to study, especially in relation to the factors behind the incident and various forms of gender violence experienced by women in Malang regency. In order to answer these questions, this research was constructed using a descriptive qualitative approach. Research data obtained from the results of field studies or observations, interviews and documentation studies. The research data were condensed as suggested by Miles, Hubberman and Saldana to obtain maximum validity of meaning. The results of the study present data that the factors causing gender-based violence in Malang district are: Factors of Lack of Fulfillment of the Family Economy, Suspicion of Infidelity, Village Community Traditions for Early Marriage, Gender Bias Opinion or Interpretation of Religion and Misogyny Culture in Village Communities, The forms of gender violence that often occur in Malang Regency society are physical, symbolic, domestic, public and economic violence